IM DILEMMA: From educators' perspective - Noor Azlinda, Zainal Abidin (2010)
The use instant messaging (IM) in language learning is seen as an alternative way in attracting students to learn English. IM is used to keep the educators up to date the latest technology as well as to ensure students' learning interest is sustained. This tool is seen as the nearest to students' interest since most of the students spend their time chatting online. This paper examines the benefits and the drawback of using instant messaging (IM) in EL T to the educators. IM has been introduced in an English course for diploma students and is also part of the assessments and practice given to students. A quantitative research was conducted among the UMP English lecturers using a set of 5-likert scale questionnaires on the use of IM in language learning. The result of the study has shown that IM can be used as a tool of communication among students as well as in motivating them in using English. However, scaffolding is still needed to be done by the teacher since IM Lingo is used widely by students. Participants are encouraged to use IM in language learning to maximize students' participation. Thus, with this approach both educators and students can benefit the use of technology in language learning but of course the presence of teacher is seen viable to monitor as well as to guide students in the activity carried out.